2018
DOI: 10.1016/j.vetmic.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Broad anti-herpesviral activity of α-hydroxytropolones

Abstract: Herpesviruses are ubiquitous in animals and cause economic losses concomitant with many diseases. Most of the domestic animal herpesviruses are within the subfamily Alphaherpesvirinae, which includes human herpes simplex virus 1 (HSV-1). Suppression of HSV-1 replication has been reported with α-hydroxytropolones (αHTs), aromatic ring compounds that have broad bioactivity due to potent chelating activity. It is postulated that αHTs inhibit enzymes within the nucleotidyltransferase superfamily (NTS). These enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…These results are consistent with our observation that raltegravir inhibited FeHV-1 replication without apparent effects on pUL15-C activity. It was also recently reported that these ␣-hydroxytropolones could inhibit the replication of a range of alphaherpesviruses, including FeHV-1 (61). They demonstrated that the compounds inhibited HHV-1 DNA replication rather than genome cleavage, similar to our observations with raltegravir.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with our observation that raltegravir inhibited FeHV-1 replication without apparent effects on pUL15-C activity. It was also recently reported that these ␣-hydroxytropolones could inhibit the replication of a range of alphaherpesviruses, including FeHV-1 (61). They demonstrated that the compounds inhibited HHV-1 DNA replication rather than genome cleavage, similar to our observations with raltegravir.…”
Section: Discussionsupporting
confidence: 90%
“…To ensure that PAA and ACV treatments were blocking viral DNA replication, we quantified viral DNA in HEp-2 cells over a 22-h time period in the presence and absence of these drugs ( Fig. 2A), using a quantitative PCR (qPCR) approach, as performed previously (63). From time zero to 3 hpi, the amounts of viral DNA were similar for all treatments and failed to increase above input levels ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Cells were treated and infected as described above. HSV-1 DNA copy numbers were calculated as described previously (63). In brief, DNA was isolated using the DNeasy blood and tissue kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…14 aHTs also have demonstrable activity against other herpesviruses including human cytomegalovirus 5b and Kaposi's sarcoma-associated herpesvirus, 21 as well as several animal herpesviruses. 22 For all these reasons, the continued development of aHTs as antiviral agents against HSV-1 is warranted.…”
Section: Biological Studiesmentioning
confidence: 99%